Dynamic changes of the gut microbial colonization in preterm infants with different time points after birth - Khan, Adnan; Mi, Hongying; Gao, Fei; Hu, Qi; Gu, Xia; Ma, Fei; Qu, LiuHong; Li, Sitao; Dai, Yiheng; Hao, Hu (Frontiers in Microbiology, 2023)
Risks associated with preterm birth are unevenly distributed across all gestations. At earlier gestational ages, complications such as necrotizing enterocolitis (NEC) and late-onset sepsis (LOS), conditions are significantly more common and are associated with a shift in the composition of the gut microbiome. In this study, we selected 12 preterm infants who were hospitalized in the Sixth Affiliated Hospital of Sun Yat-sen University from (January 2017 to December 2017) to describe the dynamic changes of intestinal flora in preterm infants at different time points (1 day, 7 days, 14 days, 21 days, 28 days, and 42 days) after birth. A total of 130 fecal specimens from preterm infants were analyzed using 16S rRNA gene sequencing. The colonization process of intestinal flora in preterm infants is highly dynamic at different time points after birth, i.e., Exiguobacterium, Acinetobacter, Bifidobacterium, and Citrobacter showed a declining abundance pattern with the advancement of age, while opportunistic pathogenic bacteria such as Klebsiella and Escherichia coli gradually grew and became the main flora during the development of intestinal flora in preterm infants. The incline in the abundance of pathogenic bacteria (Klebsiella and Escherichia coli), drug-resistant bacteria (Cryseobacterium), and decline of Bifidobacterium in the intestinal flora of preterm infants in the neonatal intensive care unit (NICU) may compromise their future health by increasing their vulnerability to infections through microbial invasion of the intestinal mucosa. Conclusively, our findings deepen our comprehension and offer new perspectives on targeting particular bacteria in the treatment of premature infants at different time points after birth.